Study experimental alat destilasi air laut terhadap kuantitas dan kualitas air tawar yang dihasilkan dengan menggunakan energi matahari - Yani, Ahmad (Universitas Muhammadiyah Metro, 2021)
One of the benefits of sunlight is to evaporate water (distillation). The working principle of this tool is that solar radiation penetrates the glass cover and hits the surface of the absorber, so that it turns into heat energy. The heat energy from the absorber is absorbed by the plate and seawater in the container in the distillation apparatus causes evaporation to occur. The water vapor produced will move up and stick to the bottom surface of the glass cover. The heat transferred to the environment causes water vapor that has reached the saturation temperature to condense. The dew that sticks to the inner surface of the glass cover will fall down by gravity following the slope of the glass cover on the outlet pipe. The purpose of this study was to determine the quantity and quality of fresh water produced by distillation equipment using solar energy. The research was conducted using an experimental method with an experimental design of a seawater distillation apparatus. The results showed that the quantity of distilled water produced from 07:00 to 16:00 for 8 days was 2578 ml. The quality of fresh water produced from the distillation apparatus includes turbidity, color, dissolved solids, temperature, taste, and odor that has met the requirements for use by the community in daily life based on the regulation of the Minister of Health of the Republic of Indonesia number 32 of 2017 concerning health quality standards. environmental and water health requirements for sanitary hygiene purposes.